2020
DOI: 10.3390/molecules25112479
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ionic Liquid Lignins Isolated from Spruce Wood with 1-Butyl-3-methylimidazolium Acetate and Methyl Sulfate and Their Binary Mixtures with DMSO

Abstract: Ionic liquids (ILs) based on 1-butyl-3-methylimidazolium (bmim) cation have proved to be promising solvents for the fractionation of plant biomass with the production of cellulose and lignin. This study deals with the characterization of lignins isolated from coniferous (spruce) wood using [bmim]OAc and [bmim]MeSO4 ionic liquids and their binary mixtures with DMSO (80:20). Molecular weight distributions, functional composition, and structural features of IL lignins were studied by size-exclusion chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Qualitative analysis of 2D HSQC NMR spectra of the studied lignins and pseudo-NMR spectra representing loading plots of the main components was carried out by comparison with data from the literature sources [5,9,22,[28][29][30][31][32]. The correctness of the identification was confirmed by the presence of all characteristic cross-peaks of the indicated fragments and the compliance of their chemical shifts with the literature data.…”
Section: Lignin Substructure Assignmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative analysis of 2D HSQC NMR spectra of the studied lignins and pseudo-NMR spectra representing loading plots of the main components was carried out by comparison with data from the literature sources [5,9,22,[28][29][30][31][32]. The correctness of the identification was confirmed by the presence of all characteristic cross-peaks of the indicated fragments and the compliance of their chemical shifts with the literature data.…”
Section: Lignin Substructure Assignmentsmentioning
confidence: 99%
“…Despite the fact that there are a large number of publications devoted to the structure of lignins of various origins [1][2][3][4][5], many aspects in this field still remain unclear due to its exceptional complexity. Naturally, the structure of lignin is primarily determined by the botanical origin of the biopolymer [5], but it also depends on the procedure used for isolating lignin preparations from the plant material [1,[6][7][8][9]. At the same time, a number of recent studies showed that lignin structure can be additionally complicated due to the incorporation of non-typical moieties, such as catechin-type phenylpropane units (C) [4] and flavonoids (for example, tricin) [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…The lignin fraction recovered aer IL pretreatment possesses a lower content of interunit ether bonds and is partly condensed. 239,240 Additionally, condensation reactions between the lignin and the IL may occur, at an extent that increases with the operating temperature. 239,240 Overall, the IL lignin fractions possess similar features to organosolv lignin streams and are regarded as a promising substrate for further upgrading toward aromatic chemicals.…”
Section: mentioning
confidence: 99%
“…Abushammala and Mao [27] emphasised the effect of IL structure on the dissolving of wood and the different challenges encountered during the dissolution process. ILs such as 1-butyl-3-methylimidazolium methyl sulfate and 1butyl-3-methylimidazolium acetate are used to fractionate biomass from plants to produce lignin and cellulose [28]. Lignin from wood can be extracted effectively using protic ionic liquid 1-methylimidazolium chloride [29].…”
Section: F Dissolution Of Woodmentioning
confidence: 99%